Nitric Oxide and the Regulation of Apoptosis in Tumour Cells - Tarr, J. M.; Eggleton, P.; Winyard, P. G. (Current Pharmaceutical Design, 2006)
Nitric oxide (NO) is a small, highly reactive, diffusible free radical which has been implicated in many physiological and pathophysiological processes. It has either pro-apoptotic or anti-apoptotic effects on cells, depending upon a host of factors. This review outlines some of the regulatory molecules and organelles involved in the apoptotic pathways that can be influenced by the presence of NO, including p53, Bcl-2, caspases, mitochondria, and heat shock proteins. The effects of NO on the apoptosis of tumour cells are also examined.
Keywords: Apoptosis